Anatomy of the energetic driving force for charge generation in organic solar cells - Kyohei Nakano (Nature Portfolio, 2019)
Understanding the energetic driving force is important for optimizing the performance of organic solar cells. Here Nakano et al. suggest that the dominant driving force is the energy difference between the singlet excited state and the charge transfer state after assessing 16 material combinations.